Long-term ecological monitoring of reefs on Hawai’i Island (2003-2020): Characterization of a common cryptic crust, Ramicrusta hawaiiensis (Peyssonneliales, Rhodophyta) - Grady, Bryant W.; Kittle, Ronald P.; Pugh, Ashley; Lamson, Megan R.; Richards, Joseph L.; Fredericq, Suzanne; McDermid, Karla J.; Allen, Quintin; Asner, Gregory P. (Frontiers in Marine Science, 2022)
The recently described crustose calcifying red algal species Ramicrusta hawaiiensis, known only from mesophotic depths off Lehua Island, west of Kaua‘i Island, was found in shallow benthic reef habitats (3-18 m deep) along the western coast of Hawai‘i Island. Molecular and microscopy techniques were used for genetic confirmation and for detailed morphological and anatomical examination. Two independent benthic cover survey datasets collected from west Hawai‘i Island were used to investigate temporal and geographic distribution of Ramicrusta. In both datasets, we report Ramicrusta at approximately 60% of the sites surveyed. Benthic cover for this alga varies among sites and among years and its presence in west Hawai‘i is evident since at least 2003. These findings help to document Hawaiian coral reef ecosystem change and benthic community composition reshuffling. This study also emphasizes the critical importance of taxonomy and proper identification of macroalgal species to understand the potential for phase-shifts of dominant taxa in coral reef ecosystems after environmental disturbances and fluctuations in abiotic factors. In the last decade, members of the red algal order Peysonnelliales have increased in abundance and overgrown other benthic species in reef ecosystems in the Caribbean and tropical Pacific. The novel aspect of finding abundant Ramicrusta in much shallower water than originally described, the decadal presence of Ramicrusta, and its potential for competition with other benthic organisms make this research valuable to coral reef ecology and justify further investigation of Ramicrusta ecology and biology in the Hawaiian Islands and globally.